The ring [videorecording (DVD)] - Verbinski, Gore; Watts, Naomi, 1968-; Henderson, Martin, 1974-; Dorfman, David; Suzuki, Kōji, 1957- (DreamWorks Home Entertainment, 2003)
A strange videotape full of bizarre and haunting images is watched by a handful of teenagers. After the viewing the tape, they receive phone calls in which they are warned they will die in seven days. Rachel, the aunt of one of the ill-fated teens, is a journalist who has decided to investigate the matter. She manages to find the cabin in the woods and watches the video herself; afterward, she receives the same phone call, and realizes she must solve the puzzle of the video and who is behind it.